Possibilities for improving hospital and remote forecasts for unstable angina - Sergey A. Boytsov; Sergei I. Provatorov (Терапевтический архив, 2024)
Unstable angina (UA) is a type of acute coronary syndrome (ACS) without ischemic myocardial damage. The main criterion for the diagnosis of UA in ACS is the absence of changes in the concentration of cardiac troponin in the patient’s blood. When the volume of myocardial damage is small, it may be difficult to detect myocardial infarction in a patient using low-sensitivity tests for determining of cardiac troponin in the blood. This issue may lead to overdiagnosis of UA in patients with non-STE ACS. Optimal drug therapy and revascularization of the coronary arteries significantly reduce the risk of death and the development of myocardial infarction both in the hospital and in the long-term period in patients with UA. Outpatient follow-up and provision of free of charge medications to patients may reduce long-term mortality after an episode of UA.